2019
DOI: 10.2136/sssaj2018.12.0476
|View full text |Cite
|
Sign up to set email alerts
|

Time Behavior of Anomalous Solute Transport in Three‐Dimensional Cemented Porous Media

Abstract: We quantitatively explore and explain the different time behavior of anomalous solute transport in three‐dimensional (3D) porous media with different cementation degrees. We find that the temporal evolution of the breakthrough curves (BTCs), spatial moments and propagators representing the time behavior of the transport varies significantly in each case with rising cementation degree. For example, the early breakthrough and long tail in the BTCs are enhanced simultaneously when the cementation degree increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…It has been observed that in many cases, two-dimensional simulation schemes can grasp the majority of the physical processes of solute transport and reduce the simulation complexity and calculation costs, compared with threedimensional simulations. In addition, in the previous study, we found that when the cementation degree increases, the velocity probability distribution of fluid in 2D media and 3D media and its change trend are similar [28,29]. Therefore, this study performed two-dimensional simulations at the pore scale for the purpose of exploring the solute dilution processes in porous media with different cementation degrees.…”
Section: Methodsmentioning
confidence: 89%
“…It has been observed that in many cases, two-dimensional simulation schemes can grasp the majority of the physical processes of solute transport and reduce the simulation complexity and calculation costs, compared with threedimensional simulations. In addition, in the previous study, we found that when the cementation degree increases, the velocity probability distribution of fluid in 2D media and 3D media and its change trend are similar [28,29]. Therefore, this study performed two-dimensional simulations at the pore scale for the purpose of exploring the solute dilution processes in porous media with different cementation degrees.…”
Section: Methodsmentioning
confidence: 89%
“…[20] reported that the fractal derivative diffusion model is suitable for simulating anomalies of moisture transport in cement-based materials. Furthermore, continuous-time random walk (CTRW) models have been confirmed to be able to explain anomalous transport in three-dimensional porous media with different cementation degrees [21]. These models use fractal geometry to describe the irregularities in a porous medium.…”
Section: Introductionmentioning
confidence: 99%
“…Trace elements have a wider applicability, and the main factor controlling the content of major and trace elements is particle size. In addition, laboratory tracing experiments are valuable tools for understanding and identifying flow and transport processes [14]. The most commonly used tracing experimental devices include soil columns and sand tanks, which are used to study the transport and hydraulic characteristics of solutes (conservative and reactive) [15], thereby gaining a deeper understanding of the trends in material transport in aquatic systems.…”
Section: Introductionmentioning
confidence: 99%